'Real men don't hit women': Constructing masculinity in the prevention of violence against women. Issue 4 (December 2016) - Salter, Michael
The primary prevention of violence against women has become a national and international priority for researchers and policy makers. While optimistic about the potential of the prevention agenda, this paper advances two related critiques of the construction of masculinities within violence against women primary prevention in high-income countries. The first is that it affords gender norms an unjustified priority over gender inequality as determinants of violence against women. The second critique is that the myopic focus of violence against women prevention efforts on gender norms results in a 'one-dimensional' view of masculinity. Nationally and internationally prominent violence against women prevention activities are grounded in a view of masculinity as a normative phenomenon disembedded from economic and political processes. As the paper argues, such a sanitised and one-dimensional account of masculinity is unable to explicable the practical steps necessary to achieve the aims of primary prevention. The paper argues that primary prevention efforts should be reorientated away from decontextualised and quasi-transcendental accounts of masculinity and towards non-violence as a suppressed possibility within the existing social order, and one that requires economic and political as well as cultural change if it is to be realised.